Summarization of the Research Status of Quadruped Robot Bionic Joint - Zhu Yaqiao; Chen Guosong; Wang Jiaojiao; Fan Guanghong (Jixie chuandong)
High speed,high mobility and high adaptability become the inevitable developing trend of quadruped robot,bionic joints as an important basis of moving parts,plays an important role about the kinematics and dynamics research of quadruped robot. Specific from four aspects of flexible pneumatic bionic joints,hydraulic damping bionic joints,series-wound elastic drive bionic joints and flexible variable stiffness bionic joints,the research status of quadruped robot bionic joints is summarized,and the various types of bionic joint defects are accurately analyzed. Finally,the future develop trend of quadruped bionic robot joints is described.With the deepening of the research,the quadruped robot bionic joint will have widely application prospect in production services,human exploration,future war and other special fields inevitably.